1996
DOI: 10.1103/physrevd.54.7153
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and inverse symmetry breaking

Abstract: An inflation model with inverse symmetry breaking of two scalar fields is proposed. Constraints on the parameters for successful inflation are obtained. In general the inequality 1 ӶgϽ 2 should be satisfied, where 1,2 and g are the coupling constants for self-interaction and mutual interaction of two scalar fields, respectively. An example with an SU͑5͒ GUT phase transition and numerical study is presented. This model introduces a new mechanism for the onset of inflation. ͓S0556-2821͑96͒05224-1͔

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The idea of ISB (or SNR) is per se a very interesting one due to its possible implementation in realistic particle physics models and its consequences in the context of high temperature phase transitions in the early Universe, with applications ranging from problems involving CP violation and baryogenesis, topological defect formation, inflation, etc (for a short list of the different applications where SNR and ISB have been used see, e.g., Refs. [2][3][4][5][6]).…”
Section: Introductionmentioning
confidence: 99%
“…The idea of ISB (or SNR) is per se a very interesting one due to its possible implementation in realistic particle physics models and its consequences in the context of high temperature phase transitions in the early Universe, with applications ranging from problems involving CP violation and baryogenesis, topological defect formation, inflation, etc (for a short list of the different applications where SNR and ISB have been used see, e.g., Refs. [2][3][4][5][6]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the final value of ξ 2 was very sensitive to its initial value, (and practically insensitive to the initial values of the other parameters), we took advantage of our accurate knowledge of κ c 2 (T = 0), and tuned the initial value of ξ 2 in such a way that κ 2 would approach the MC value of κ c 2 (T = 0) in the limit ξ 2 → ∞. The initial value of ξ 2 that we obtained in this way, ξ 2 = 11.85 (5), is very close to the MC one, as can be seen from Table 2. The value of ξ 2 at p turned out to be ξ 2 (p) = 45(5): the error is basically due to the uncertainty in the MC values of κ c 2 (T = 0) and κ c 2 (N t = 2).…”
Section: Comparison With Perturbation Theorymentioning
confidence: 99%
“…This is not the right place to discuss these very interesting applications of ISB and SNR, but to give the reader an idea of the number and relevance of the issues that have been treated , we just make a list and quote some references. Following the historical order, ISB and SNR were applied to: the breaking of CP symmetry [2], the monopole problem [3], baryogenesis [4], inflation [5], the breaking of P, strong CP and Peccei-Quinn symmetries [6] and finally supersymmetry [7].The potential importance of ISB and SNR for cosmology induced several authors to study these phenomena more accurately, than was done in Weinberg's original paper. His analysis relied, in fact, on a simple one-loop computation, and so it was natural to question if higher order corrections would have changed the scenario.…”
mentioning
confidence: 99%
“…To make this seemingly paradoxical statement more plausible, the author observed that in Nature there exists at least one substance, the Rochelle salt, which does exhibit this type of "inverse" behavior in a certain range of temperatures and thus the expectation that more heat necessarily means more disorder is clearly not always true. In any case, these remarks of Weinberg passed totally unnoticed, until some authors resumed this idea, applying it to important cosmological questions like the domain wall and monopole problems [5,6,7,8], the breaking of the CP symmetry [9], baryogenesis [10], inflation [11] and the breaking of the P, Strong CP and the Peccei-Quinn symmetries [12]. Recently, the possibility of ISB and SNR also in supersymmetric models has been explored [13].…”
Section: Introductionmentioning
confidence: 99%